Methodology of software development with the use of the model of distributed object-based stochastic hybrid systems - R. Е. Sharykin (Informatika)
Software development methodology based on the model of distributed object-based stochastic hybrid systems is proposed. Such mathematical model is planned to be created for the system being designed along with the system specification at all stages of the software development.The following stages of the development are considered as building of preliminary mathematical model by designing its specification, choosing and specification of system metrics, statistical analysis of the model, approbation of the mathematical model in conditions close to real, analysis by analytical methods and the implementation. The formalism is proposed for describing the system under consideration and an approach to its analysis. At the steps of the methodology, we adjust the model specification and its corresponding mathematical model in accordance with the results of the analysis. This approach allows to develop not only the software, but also a mathematical model with its properties, which implementation is the resulting software.